Pencegahan Dampak Lingkungan Pada Industri Pewarnaan Melalui Pendekatan Penilaian Siklus Daur Produk - Reki Detiar; Nabila Ardiana; Novena Lany Pangestu; Ziyadatulkhair M.Faruqi; Ardhan Ardianto; Nurulbaiti Listyendah Zahra; I Wayan Koko Suryawan (Fakultas Teknik, 2021)
The home-scale coloring industry is currently starting to develop with various models and effects which result in the production of various phases of solid, liquid, and gas emissions. The purpose of this study is to measure the environmental impact and ensure that life management minimizes the impact of recycling industrialdye . This research was conducted by direct industry observation methods and a literature review on the management of industrial waste. Environmental impact calculations were completed carried out using the 2018 Environmental Product Declaration (EPD) method on SimaPro 9.1.1 with an ecoinvent 3 database. The results of the environmental impact assessment should be managed according to the effects of water scarcity, acidification, and eutrophication. Pollution prevention can occur by treating industrial wastewater dye . Wastewater treatment can be performed by biological processes based on the biodegradability index. The biodegradability index of 0.3 indicates that wastewater can be treated by the activated sludge process and by moving the bed biofilm reactor (MBBR).